KEPEMIMPINAN TRANSFORMASIONAL, KEPUASAN KERJA DAN KOMITMEN ORGANISASI SEBAGAI MOTIVATOR KINERJA PEGAWAI NEGERI SIPIL - Gerry Suryosukmono (Unib Press Universitas Bengkulu, 2020)
Greater autonomy give a more responsibility for region to fulfill people’s needs. At consequences, productivity and performance of public employee become a main factor that must be solved. This study aimed to analyze the effect of transformational leadership, job satisfaction and organizational commitment to increase the degree of job performance from public service employees in Bengkulu City. Sample of research include 60 civil servants in the Local Government Unit (SKPD) Bengkulu from Regional Employment Agency (BKD), Regional Development Planning Agency (Bappeda), Narcotics Board (BNN Kota Bengkulu) and Kesbanglinmas using multiple regression analysis. Sample determined by convenience sampling method. This research concludes that transformational leadership, job satisfaction and organizational commitment have significant effect on employee performance in public sector of Bengkulu City . Implications for research and managerial practices were derived from these findings.Keyword: Transformational Leadership; Job Satisfaction; Organizational Commitment; Employee PerformanceAbstract Greater autonomy give a more responsibility for region to fulfill people’s needs. At consequences, productivity and performance of public employee become a main factor that must be solved. This study aimed to analyze the effect of transformational leadership, job satisfaction and organizational commitment to increase the degree of job performance from public service employees in Bengkulu City. Sample of research include 60 civil servants in the Local Government Unit (SKPD) Bengkulu from Regional Employment Agency (BKD), Regional Development Planning Agency (Bappeda), Narcotics Board (BNN Kota Bengkulu) and Kesbanglinmas using multiple regression analysis. Sample determined by convenience sampling method. This research concludes that transformational leadership, job satisfaction and organizational commitment have significant effect on employee performance in public sector of Bengkulu City . Implications for research and managerial practices were derived from these findings.Keyword: Transformational Leadership; Job Satisfaction; Organizational Commitment; Employee Performance